FOSTERING QUALITY TEACHERS UNDER THE SETTING OF INDONESIAN CLASSROOMS - Kartika Nuswantara (JURNAL SOSIAL HUMANIORA (JSH), 2013)
Being a teacher could be committed by anyone who has the passion in teaching, so that any situations in reality would not hamper him from the struggle to be a good teacher. Classroom is the laboratory for the teachers for their personal development. Students from whom the teachers can learn are their other assets. If an unfortunate system keeps going without any authority from the side of the teacher to change, being a quality teacher should still become teachers’ efforts to realize.